2018
DOI: 10.1371/journal.pone.0205014
|View full text |Cite
|
Sign up to set email alerts
|

Pathological alleles of MPV17 modeled in the yeast Saccharomyces cerevisiae orthologous gene SYM1 reveal their inability to take part in a high molecular weight complex

Abstract: Mitochondrial DNA depletion syndromes (MDDS) are a genetically and clinically heterogeneous group of human diseases caused by mutations in nuclear genes and characterized by a severe reduction in mitochondrial DNA (mtDNA) copy number leading to impaired energy production in affected tissues and organs. Mutations in the MPV17 gene, whose role is still elusive, were described as cause of the hepatocerebral form of MDDS and Navajo neuro-hepathopathy. The high degree of conservation observed between MPV17 and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…First, as already reported by D'Agati et al (2017), we confirmed that zebrafish mpv17 mRNA can rescue the mpv17 −/− mutant phenotype, and, most importantly, that human MPV17 mRNA also has similar properties in vivo , thus supporting a conserved function of the two orthologues; this finding is also in agreement with complementation assays in the yeast sym1 Δ model (Trott and Morano, 2004), showing a functional link between Sym1 and mammalian MPV17. In addition, a recent work demonstrated that the growth of sym1 Δ strain transformed with R51Q (hR50Q) mutant Sym1-HA allele was impaired (Gilberti et al, 2018). In agreement, also in zebrafish, the injection of the p. R50Q mutated form of human MPV17 mRNA resulted in a mild rescue of the mpv17 −/− KO phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…First, as already reported by D'Agati et al (2017), we confirmed that zebrafish mpv17 mRNA can rescue the mpv17 −/− mutant phenotype, and, most importantly, that human MPV17 mRNA also has similar properties in vivo , thus supporting a conserved function of the two orthologues; this finding is also in agreement with complementation assays in the yeast sym1 Δ model (Trott and Morano, 2004), showing a functional link between Sym1 and mammalian MPV17. In addition, a recent work demonstrated that the growth of sym1 Δ strain transformed with R51Q (hR50Q) mutant Sym1-HA allele was impaired (Gilberti et al, 2018). In agreement, also in zebrafish, the injection of the p. R50Q mutated form of human MPV17 mRNA resulted in a mild rescue of the mpv17 −/− KO phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Both genes encode for a small protein localised to the inner mitochondrial membrane, whose function is not yet fully understood. The impact of seven pathological missense mutations, localised in different protein domains, on correct mitochondrial localisation was assessed demonstrating that the mutated residues do not compromise protein import [ 75 ].…”
Section: Validation Of Mutations and Understanding Of Pathogeneticmentioning
confidence: 99%
“…With the same technique, it was demonstrated that Sym1, the equivalent of MPV17, takes part in a high molecular–weight complex of which the composition is still unknown [ 251 ]. Furthermore, the impact of seven MPV17/SYM1 missense mutations was assessed showing that six of them compromised the formation of the fully assembled complex [ 75 ].…”
Section: Validation Of Mutations and Understanding Of Pathogeneticmentioning
confidence: 99%
“…Thanks to the high degree of conservation between human MPV17 protein and its yeast homolog Sym1, several sym1 mutant alleles have been previously constructed by introducing human MPV17 mutations in the corresponding position of the SYM1 gene [4,34].…”
Section: Identification Of Molecules Preventing the Oxidative Phosphorylation Defect Associated With The Sym1 Mutationmentioning
confidence: 99%
“…The sym1∆ strain and all the strains carrying mutations equivalent to the pathological alleles present in humans studied so far, are characterized by a significant increase of petite mutants [4,34]. These mutants arise spontaneously in the presence of large deletions or a depletion of mtDNA which gives rise to mitochondrial respiratory deficient cells [35].…”
Section: Characterization Of the Effects Of The Identified Molecules On Mtdna Maintenancementioning
confidence: 99%